Implementasi Metode Prototype dalam Analisis Perancangan Sistem Informasi Pengajuan Pembiayaan Berbasis Web Pada Bank Muamalat Cabang Situbondo (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The development of information technology has brought significant changes in various sectors, especially in the banking sector. However, the financing application service at the Muamalat Bank Situbondo Branch still uses manual methods that are inefficient and risky. This study aims to design a web-based financing application information system using the Prototype method, which can produce an information system design with a simple, user-friendly, and easy-to-operate interface, so that customers and bank officers can quickly understand the flow of use. In this study, the method used is a qualitative descriptive method with a case study approach. Data collection techniques include interviews with agency supervisors, direct observation in the field, and documentation. The results obtained from this study are an information system design that includes process modeling (UML), database modeling (Class Diagram), and user interface design. This system is designed to allow customers to apply for financing online, upload digital documents, and monitor the application status in real time. With this system, it is expected that the process of data verification and validation by bank employees will be faster and more accurate, and the risk of document loss can be minimized.